Value Chain Analysis of Onion in Dugda District, Oromia Region, Ethiopia - Dawit Hailegiorgis (Archives of Current Research International, 2017)
The study on onion value chain primarily aimed to identify the actors in the value chain, quantify actors costs and profit margin and identifying constraints and causes of the main problem. The data was generated by mainly desk study from a wide range of secondary sources such as books and journals, internet services using Google and Google scholar and unpublished sources. The study finding shows that onion value chain actors include input suppliers, producers, collectors, farmer-traders, middlemen/brokers, wholesalers, retailers, consumers whereas the identified chain supporters include the Ministry of Agriculture and Natural Resources (MoANR), Small and Micro Financial Institutions (SMFI), District Irrigation Development Authority (DIDA), Awash Melkasa Agricultural Research Center (AMARC). About five channels of onion marketing were identified and out of five, two market channels (II & III) were found to be dominant in terms of volume of the transaction which accounts 74.2% and 21.2%, respectively. The study also identified the value addition/kg of onion; where central retailers and central wholesalers had the highest share but farmer-trader had the least value. Central retailer obtained the highest profit share (31%) per kg; however, farmer-trader attained the least profit share per kg which is about 19%. The main constraints identified include; price fluctuation, lack of credit availability, scarcity of fertilizers, less availability of inputs, high onion seed cost which is caused by the existence of an oligopolistic market, high involvement of brokers and less awareness of farmers about the market. Recommendation drawn from the study findings necessitate changing the oligopolistic market structure, changing the role of brokers in the market and supporting local onion markets.